Design and Testing of a solar Parabolic Trough System for Electricity Generation in Sudan (University of Khartoum Engineering Journal, 2022)
The performance characteristics of a parabolic trough collector system have been characterized using ASHRAE 93 standard. The standard includes collector efficiency test and the incident angle modifier test. The fabricated trough-receiver unit and its down stream system were installed in an open area at the roof of the Mechanical Engineering Department, University of Khartoum. The test result shows that the obtained thermal efficiency is 32%. The output shows that it is possible to generate electricity using parabolic trough system with a considerable efficiency and competitively with the other conventional systems due to high local solar potential through the year and availability of site areas